Civic Education as Strategies to Strengthen the National Identity of Indonesian Students - Rizky, Widya Alfa; Tsaqila, Diena Qaulan; Nelwati, Sasmi (Perwakilan: Journal of Good Governance, Diplomacy, Customary Institutionalization and Social Networks, 2024)
This study explores comprehensive strategies to strengthen national identity among Indonesian students, addressing the crucial need for a cohesive national identity in Indonesia's ethnically and culturally diverse society. The research identifies and analyzes several key approaches, including curriculum development, extracurricular activities, cultural immersion programs, and the use of digital media, to foster a strong sense of national pride and unity. The integration of national history, civic education, and values into the school curriculum is highlighted as fundamental. By ensuring that students receive a thorough understanding of Indonesia's heritage, struggles for independence, and national achievements, educational institutions can instil a deep sense of belonging and responsibility towards the nation. Extracurricular activities, such as student organizations, sports, arts, and community service projects, are also emphasized for their role in providing experiential learning opportunities that reinforce national values and social cohesion. Cultural immersion programs are identified as another critical strategy. These programs, which include traditional arts, music, dance, and language preservation initiatives, allow students to engage with Indonesia's rich cultural tapestry, fostering appreciation and respect for the nation's diversity. Furthermore, the strategic use of digital media is examined as a modern approach to connecting students across different regions and promoting national narratives. Digital platforms can disseminate stories of national heroes, cultural heritage, and contemporary achievements, thereby enhancing students' collective national consciousness. The study underscores the importance of a multifaceted approach involving educational institutions, government policies, and community participation. It recommends that policymakers and educators collaborate to implement these strategies effectively, creating an environment that nurtures a strong, cohesive national identity among Indonesian youth. By doing so, the nation can build a resilient and unified future generation capable of contributing positively to Indonesia's development and stability.